PENGARUH INDEK PENGEMBANGAN MANUSIA (IPM) TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR 2022-2023 - Haryono, Basuki; Margono, Hery (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This quantitative research aims to investigate the relationship between Human Development Index (HDI) and Economic Growth across 38 districts in East Java, Indonesia, using data from Badan Pusat Statistik for the years 2022-2023. The study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) methodology using SmartPLS to analyze the data. The path analysis revealed a statistically significant positive relationship between HDI and Economic Growth, suggesting that improvements in human development contribute significantly to economic advancement in the region. Based on these findings, recommendations include enhancing investments in education, healthcare, and infrastructure to further strengthen human capital and stimulate economic growth in East Java.